2019
DOI: 10.1002/oby.22648
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Role of Health Behaviors, Socioeconomic Status, and Cumulative Stress for Racial/Ethnic Disparities in Obesity

Abstract: Objective This study aimed to examine the explanatory role of health behaviors, socioeconomic position (SEP), and psychosocial stressors on racial/ethnic obesity disparities in a multiethnic and multiracial sample of adults. Methods Using data from the Chicago Community Adult Health Study (2001‐2003), Oaxaca‐Blinder decomposition analysis was conducted to quantify the extent to which health behaviors (fruit and vegetable consumption and physical activity), SEP, and cumulative stressors (e.g., perceived discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 40 publications
2
36
0
1
Order By: Relevance
“…Our 1st result is in-line with what we know about parental education's role as a social determinant of health in general (Cuevas et al, 2020;Williams, 1999) and brain development in particular (Brody et al, 2017;Farah, 2018;Hackman et al, 2013;Hackman & Farah, 2009;Hackman, Farah, & Meaney, 2010;Hanson, Chandra, Wolfe, & Pollak, 2011; "Poverty and brain development", 2015). Marmot (2005;Singh-Manoux, Richards, & Marmot, 2005;Stringhini et al, 2018), Phelan (1995, 2009;Phelan, Link, Diez-Roux, Kawachi, & Levin, 2004), Mirowsky and Ross (2015;Ross & Mirowsky, 2011), and many other investigators (Cuevas et al, 2020;Williams, 1999) performance (Assari, 2019c;Assari & Caldwell, 2019b), ADHD (Assari & Caldwell, 2019a), anxiety (Assari, Caldwell, & Zimmerman, 2018), obesity (Assari, Thomas, et al, 2018), and health (Assari, Caldwell, & Mincy, 2018b) Risk of poor mental and physical health outcomes, such as depression, anxiety, suicide, chronic disease, and obesity, also remains high in high SES Black American children ( Assari, 2018f;Assari & Caldwell, 2019a;. Similar MDRs (Assari, 2017c) are shown for children (S. Assari, 2018d;…”
Section: Discussionsupporting
confidence: 87%
“…Our 1st result is in-line with what we know about parental education's role as a social determinant of health in general (Cuevas et al, 2020;Williams, 1999) and brain development in particular (Brody et al, 2017;Farah, 2018;Hackman et al, 2013;Hackman & Farah, 2009;Hackman, Farah, & Meaney, 2010;Hanson, Chandra, Wolfe, & Pollak, 2011; "Poverty and brain development", 2015). Marmot (2005;Singh-Manoux, Richards, & Marmot, 2005;Stringhini et al, 2018), Phelan (1995, 2009;Phelan, Link, Diez-Roux, Kawachi, & Levin, 2004), Mirowsky and Ross (2015;Ross & Mirowsky, 2011), and many other investigators (Cuevas et al, 2020;Williams, 1999) performance (Assari, 2019c;Assari & Caldwell, 2019b), ADHD (Assari & Caldwell, 2019a), anxiety (Assari, Caldwell, & Zimmerman, 2018), obesity (Assari, Thomas, et al, 2018), and health (Assari, Caldwell, & Mincy, 2018b) Risk of poor mental and physical health outcomes, such as depression, anxiety, suicide, chronic disease, and obesity, also remains high in high SES Black American children ( Assari, 2018f;Assari & Caldwell, 2019a;. Similar MDRs (Assari, 2017c) are shown for children (S. Assari, 2018d;…”
Section: Discussionsupporting
confidence: 87%
“…Association between Parental Education and Childhood Body Mass Index by Race4. DiscussionAlthough higher family SES (parental education) is associated with a reduced childhood BMI (1st finding), family SES shows a weaker effect for non-White and White children (2nd finding).Our 1st result is in line with what we know about parental education's role as a social determinant of health in general(Cuevas et al, 2020;Williams, 1999) and obesity in particular(Chaparro & Koupil, 2014;Cook & Tseng, 2019;Eidsdottir, Kristjansson, Sigfusdottir, Garber, & Allegrante, 2013;Elinder, Heinemans, Zeebari, & Patterson, 2014; Lamerz et al, 2005;Matthiessen et al, 2014) Marmot(2005),Singh-Manoux, Richards andMarmot (2005),Stringhini et al (2018), Phelan (1995, 2009),Phelan, Link, Diez-Roux, Kawachi and Levin (2004),Mirowsky and Ross (2015),Ross and Mirowsky …”
supporting
confidence: 86%
“…This model showed that parental education and race interact, meaning that the effect of parental education on BMI was weaker for non-White than White children ( Figure 3). (2011) and many other investigators (Cuevas et al, 2020;Williams, 1999) Showell et al, 2017;Stewart-Knox et al, 2012). High family SES also reduces the environmental risk of obesity, as high SES families live in less obesogenic environments (Choi et al, 2016;Crespi, Wang, Seto, Mare, & Gee, 2015;Dulin-Keita, Kaur Thind, Affuso, & Baskin, 2013;Forsyth et al, 2015).…”
mentioning
confidence: 94%
“…Low family SES is also a proxy of poor parenting [ 64 , 65 , 66 , 67 , 68 ] and high parental risk behaviors [ 69 , 70 ] that can put child brain development in jeopardy [ 71 ]. Secondary to these cumulative risks, adolescents from low SES families remain at high level of risk of psychopathologies [ 72 , 73 , 74 ], problem behaviors [ 75 , 76 , 77 , 78 , 79 , 80 , 81 ], and poor school performance [ 82 , 83 , 84 ].…”
Section: Introductionmentioning
confidence: 99%